Efficient serum-free derivation of oligodendrocyte precursors from neural stem cell-enriched cultures - Rao, Rajesh C. (Stem Cells, 2009)
Oligodendrocytes derived in the laboratory from stem cells have been proposed as a treatment for acute and chronic injury to the central nervous system. Platelet-derived growth factor-receptor alpha (PDGFRα) signaling is known to regulate oligodendrocyte precursor cell numbers both during development and adulthood. Here, we analyze the effects of PDGFRα signaling on central nervous system (CNS) stem cell-enriched cultures. We find that AC133 selection for CNS progenitors acutely isolated from the fetal cortex enriches for PDGF-AA responsive cells. PDGF-AA treatment of FGF2-expanded CNS stem cell-enriched cultures increases nestin+ cell number, viability, proliferation, and glycolytic rate. We show that a brief exposure to PDGF-AA rapidly and efficiently permits the derivation of O4+ oligodendrocyte-lineage cells from CNS stem cell-enriched cultures. The derivation of oligodendrocyte-lineage cells demonstrated here may support the effective use of stem cells in understanding fate choice mechanisms and the development of new therapies targeting this cell type.